A review of fuel cell technology for commercial vehicle applications. (15th February 2022) - Jokela, Tommi; Kim, Bill; Gao, Bo; Wellers, Matthias; Peng, Zhijun
The demanding energy storage requirements of many commercial vehicle applications are extremely difficult to meet for pure battery electric vehicles (BEVs) due to the limited energy density of batteries. Fuel cells appear to be the only viable propulsion technology that is able to meet commercial vehicle powertrain requirements with zero local greenhouse gas emissions. Since almost all fuel cell vehicles (FCVs) contain a high voltage battery, some additional complexity is introduced since the hybrid energy storage system must be sized and controlled appropriately. An understanding of the strengths and weaknesses of each system is therefore essential in FCV design. The aim of this technology review is to provide an overview of fuel cell technologies in commercial vehicle applications including assessments of alternative powertrain and fuel cell types, advantages and disadvantages of fuel cell and battery systems and the implications of these on the powertrain sizing as well as control considerations of FCVs.